PENGARUH FUNDAMENTAL MAKROEKONOMI TERHADAP CADANGAN DEVISA INDONESIA STUDI KASUS PADA MASA PANDEMI COVID-19 - Sudiksa, I Wayan Dipa; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024, 2024)
This study aims to analyze the factors that affect Indonesia's devenom reserves during the Covid-19 pandemic with the data used, namely the time series for the period of January 2019 to October 2022. The method used in this study is the Error Correction Model (ECM) regression to see the short-term and long-term influence on the independent variable on the dependent variable. The results of this study show that simultaneously short-term and long-term variables of net exports, exchange rates, inflation and the Covid-19 pandemic have a significant effect on foreign exchange reserves. While partially in the short term the net export variable has a negative and insignificant effect, while in the long run it has a positive but not significant effect. Exchange rate variables partially in the short and long run have a negative and significant effect. Then the variable inflation partially in the short and long term has a positive and insignificant effect. And the dummy variable of Covid-19 has a positive and insignificant effect in the short term, then a positive and significant effect in the long term.